Development of Silicon Nanowire Array–Metal Hybrid Catalysts for Batch and Flow Organic Reactions - Baek, Heeyoel; Yamada, Yoichi M. A. (Synlett, 2023)
The development of highly efficient and reusable supported metal catalysts is important for academic and industrial synthetic organic chemistry; however, their widespread application remains a challenge because supported Pd, Rh, and Pt catalysts are expensive. To overcome these problems, we have developed novel, highly stable, reusable, and selective heterogeneous catalysts consisting of silicon nanowire arrays (SiNAs) and metal nanoparticle composites. Metal nanoparticles on SiNA have been applied as heterogeneous catalysts in the Mizoroki–Heck reaction, C–H arylation, hydrosilylation, hydrogenation, reductive alkylation of amines, and hydrogenative decarboxylation of fatty acids. The catalysts used in this study showed high catalytic activity in batch and microflow conditions. Their structural investigation using X-ray Photoelectron Spectroscopy (XPS) suggests that strong metallic bonding (alloy/agglomeration) between the metal and silicon (metal silicide bond formation) is key to the high catalyst stability.1 Introduction2 Development of Silicon Nanowire Array (SiNA) Hybrid Catalysts and Silicon Nanostructure (SiNS) Hybrid Catalysts3 Application of SiNA-Pd to Organic Synthesis4 SINA-Supported Mono- and Bimetallic Nanoparticles for Hydrogenation Reactions5 Application of SiNA-Pd to Microflow Reductive Alkylation Reactions6 Application of SiNA-Rh to Hydrogenative Decarboxylation Reactions using Microwave Irradiation7 Conclusions
Keywords: heterogeneous catalyst; silicon nanowire array; hydrogenation; bio hydro-fined diesel; microflow reaction; metal nanoparticle